Pengaruh Model Pembelajaran Predict Observe Explain (POE) Berbantuan Media Pembelajaran Interaktif terhadap Kemampuan Berpikir Kritis Ditinjau dari Motivasi Belajar Siswa Kelas X SMA Batik 1 Surakarta - Annissa Annissa; Soetarno Soetarno; Aniek Aniek (Departement of Mathematics Education, 2024)
This study aims to (1) determine the differences in the results of students' critical thinking skills using the POE learning model and the make a match learning model; (2) determine the differences in the results of students' critical thinking skills with high learning motivation and low learning motivation; (3) determine the interaction of the influence of the use of learning models and learning motivation on students' critical thinking skills. This study is a quantitative quasi-experimental study with a population of class X students of SMA Batik 1 Surakarta. The sampling technique used cluster random sampling and obtained two samples X4 (41 students) as the experimental class and X7 (42 students) as the control class. The data collection technique used the results of the pre-test, post-test, and motivation questionnaire. The data analysis technique used Anova Two Ways. The results of the study showed (1) there were differences in the results of critical thinking skills between the application of the POE learning model assisted by interactive learning media and the make a match model; (2) There was no difference in the results of critical thinking skills between the learning motivation of high and low category students; (3) there was no influence between the learning model and learning motivation on students' critical thinking skills.